`f''(theta)=sin(theta)+cos(theta)`

`f'(theta)=int(sin(theta)+cos(theta))d(theta)`

`f'(theta)=-cos(theta)+sin(theta)+C_1`

Now let's find constant C_1 , given f'(0)=4

`f'(0)=4=-cos(0)+sin(0)+C_1`

`4=-1+0+C_1`

`C_1=5`

`:.f'(theta)=-cos(theta)+sin(theta)+5`

`f(theta)=int(-cos(theta)+sin(theta)+5)d(theta)`

`f(theta)=-sin(theta)-cos(theta)+5(theta)+C_2`

Now let's find constant C_2 , given f(0)=3

`f(0)=3=-sin(0)-cos(0)+5(0)+C_2`

`3=-0-1+C_2`

`C_2=4`

`:.f(theta)=-sin(theta)-cos(theta)+5(theta)+4`

## See

This Answer NowStart your **subscription** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

`f''(theta)=sin(theta)+cos(theta)`

`f'(theta)=int(sin(theta)+cos(theta))d(theta)`

`f'(theta)=-cos(theta)+sin(theta)+C_1`

Now let's find constant C_1 , given f'(0)=4

`f'(0)=4=-cos(0)+sin(0)+C_1`

`4=-1+0+C_1`

`C_1=5`

`:.f'(theta)=-cos(theta)+sin(theta)+5`

`f(theta)=int(-cos(theta)+sin(theta)+5)d(theta)`

`f(theta)=-sin(theta)-cos(theta)+5(theta)+C_2`

Now let's find constant C_2 , given f(0)=3

`f(0)=3=-sin(0)-cos(0)+5(0)+C_2`

`3=-0-1+C_2`

`C_2=4`

`:.f(theta)=-sin(theta)-cos(theta)+5(theta)+4`